Anthropo-theology of Johann Heinrich Schütte - Drozdek, Adam (Studia Teologiczne Białystok Drohiczyn Łomża, 2023)
Johann Heinrich Schütte was an eighteenth-century physician who was keenly interested in theology and, in the spirit of the then reigning physico-theology, he was convinced his profession can contribute to theology; he authored a book on anthropo-theology in which he showed that all aspects of the human life – physical, spiritual, and social – are a clear proof of the existence of God and of His providential care for His creation.